Narcissism, Entitlement, and Questionable Research Practices in Counseling: A Pilot Study - Wester, Kelly L. (Journal of counseling and development, 2008)
Although reports of research misconduct and questionable research practices (QRPs) have been prevalent in the literature, very little has been written about these issues in the field of counseling. The current pilot study addresses (a) the continuous drive for evidence-based practice in education and counseling and (b) the relationship between QRPs and individual characteristics. QRPs are reported for the sample, indicating that this does exist, at least minimally, within the field of counseling. The authors also explored the role of demographic and specific personality characteristics in explaining QRPs